👤

Pomoze ktos
(–4) – 5 ∙ (–3)
b) (–32) : 8 – (–2)
c) (–6) ∙ 3 – 5
d) (–7) – 14 + (–1)
e) [(–9) – 16] ∙ (–3)
f) 16 : [(–3) – (–1)]
g) (–2) – (–4) ∙ (–2)
h) (–9) + (–6) : (–3)
i) (–8) ∙ 2 – (–4)
j) (–10) + 14 : (–2)
k) 15 – 7 ∙ (–2)
l) 9 – (–24) : (–6)


Odpowiedź :

Odpowiedź:

[tex]a)\ \ (-4)-5*(-3)=-4+15=11\\\\b)\ \ (-32):8-(-2)=-4+2=-2\\\\c)\ \ (-6)*3-5=-18-5=-23\\\\d)\ \ (-7)-14+(-1)=-7-14-1=-22\\\\e)\ \ [(-9)-16]*(-3)=(-9-16)*(-3)(-25)*(-3)=75\\\\f)\ \ 16:[(-3)-(-1)]=16:(-3+1)=16:(-2)=-8\\\\g)\ \ (-2)-(-4)*(-2)=-2-8=-10\\\\h)\ \ (-9)+(-6):(-3)=-9+2=-7\\\\i)\ \ (-8)*2-(-4)=-16+4=-12\\\\j)\ \ (-10)+14:(-2)=-10-7=-17\\\\k)\ \ 15-7*(-2)=15+14=29\\\\l)\ \ 9-(-24):(-6)=9+24:(-6)=9-4=5[/tex]